2012
DOI: 10.1111/jdv.12001
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, waist circumference, weight change and the risk of psoriasis in US women

Abstract: Background Psoriasis is a common chronic inflammatory skin disorder. Higher adiposity may increase the risk of psoriasis, but prospective data on this association are scarce. One prospective study showed that increased adiposity increased the risk of incident psoriasis in younger women, but no data are available in older women. Methods We prospectively examined the associations between body mass index (BMI), weight change, waist and hip circumference and risk of incident psoriasis in 67,300 women over a 12-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 26 publications
9
80
2
5
Order By: Relevance
“…The prospective longitudinal data from incident case analysis implies that increased BMI precedes the onset of psoriasis. 7 …”
Section: Resultsmentioning
confidence: 99%
“…The prospective longitudinal data from incident case analysis implies that increased BMI precedes the onset of psoriasis. 7 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, prospective cohort studies have demonstrated that higher BMI is associated with incident psoriasis and weight gain 13,14 , along with incident psoriatic arthritis 15 . Furthermore, a prospective randomized trial reported that diet-induced weight loss for 8 weeks reduced the disease severity in 60 overweight patients with psoriasis 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In studies of incident psoriasis, 6870 the risk of psoriasis was found to increase with higher BMI. 69 A meta-analysis of 16 observational studies found a pooled odds ratio [OR] for the association between psoriasis and obesity to be 1.66 (95% confidence interval [CI] 1.46–1.89) (Table II). 71 Among studies that accounted for psoriasis severity, generally defined by treatment patterns, the pooled ORs for the association between obesity and mild and severe psoriasis were 1.46 (95%CI 1.17–1.82) and 2.23 (95% CI 1.63–3.05), respectively.…”
Section: Cardiometabolic Diseasementioning
confidence: 99%